2018
DOI: 10.1097/scs.0000000000004251
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Conditioned Medium Obtained From Calvaria, Mandible, and Tibia Cause an Equivalent TGF-β1 Response In Vitro

Abstract: Bones with different embryological origin and mode of ossification are supposed to vary in their capacity for supporting graft consolidation. The aim of the current pilot study was to assess the TGF-β1 activity of bone chips obtained from distinct anatomic locations. Conditioned medium was prepared from bone chips harvested from pig calvaria, mandible, and tibia. Human oral fibroblasts were exposed to bone-conditioned medium (BCM) followed by reverse transcriptase polymerase chain reaction of the TGF-β1 target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…To understand if the embryologic origin of bone affects the activity of the respective ABL, bone chips were prepared from the mandible, the calvaria and the tibia 25 . All three independent preparations stimulated the expression of IL11, PRG4 and NOX4 in oral fibroblasts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To understand if the embryologic origin of bone affects the activity of the respective ABL, bone chips were prepared from the mandible, the calvaria and the tibia 25 . All three independent preparations stimulated the expression of IL11, PRG4 and NOX4 in oral fibroblasts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…First, to assess the osteogenic effect of the materials in one of the most common bone reconstruction scenarios in oral implantology, the horizontal bone augmentation, we prepared buccal alveolar crest defect models in beagle dogs to mimic the clinical GBR surgery. When it comes to choosing the donor sites of CanBC and CorBC, it is widely recognized that embryological origin and mode of ossification affect the clinical properties of bone grafts (Hatami Kia et al, 2018). Cranial bones are derived from neural crest cells mainly via intramembranous ossification, while most long bones are mesoderm‐derived through endochondral ossification (Chai et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some research verify that autografts contain a paracrine‐like regulatory function (Caballé‐Serrano et al, 2017; Zimmermann et al, 2015). Previous studies have shown that some growth factors like bone morphogenetic proteins (BMPs) are entombed in the matrix, thus the bone conditioned medium from pig mandibular cortical bone contains a large array of proteins, which can target mesenchymal cells involved in bone regeneration (Caballé‐Serrano et al, 2015; Hatami Kia et al, 2018; Parisi et al, 2021; Zimmermann et al, 2015).…”
Section: Discussionmentioning
confidence: 99%